Giardia duodenalis in Wildlife: Exploring Genotype Diversity in Italy and across Europe - Isabel Guadano Procesi; Margherita Montalbano Di Filippo; Claudio De Liberato; Andrea Lombardo; Giuseppina Brocherel; Stefania Perrucci; David Di Cave; Federica Berrilli (Pathogens, 2022)
Fragmented data are so far available on genotype diversity of G. duodenalis in wildlife in different countries in Europe, in particular, in Italy. In the present study, G. duodenalis sequences obtained from different Italian wild animals [12 porcupines (Hystrix cristata), 4 wild boars (Sus scrofa), 1 wolf (Canis lupus italicus), 6 Alpine chamois (Rupicapra rupicapra rupicapra)] were compared with those available from wild host species in Europe to add new data on the geographic distribution of Giardia assemblages/sub-assemblages and their transmission patterns among natural hosts. Thirty-eight sequences were obtained by MLG analysis (SSU-rRNA, bg, gdh, and tpi genes) and subsequently compared by phylogenetic and network analyses with those from wild species monitored in the last decades in Europe. The results revealed the presence of potentially zoonotic (A-AI, A-AII from wild boar; B from porcupine) and host-adapted (D from wolf; E, A-AIII from chamois) assemblages and sub-assemblages and represent the first report for Italian wild boar. The analysis did not find any evidence of spatial or host segregation for specific genetic variants, mostly shared between different hosts from different European countries. However, conflicting evidence was found in genotypic assignment, advocating for data improvement and new genomic approaches.